Asn384Ser Mutation in Protein C is Associated with Multiple-Site Thrombosis in a Young Heterozygous Male - Yuan, Junwei; Zhou, Shijie; Wu, Xi; Li, Fang; Lai, Zhe; Ding, Qiulan; Wu, Wenman; Wang, Xuefeng; Dai, Jing; Hu, Xiaobo; Lu, Yeling (Thrombosis and Haemostasis, 2025)
Protein C (PC) is an important physiological anticoagulant factor in humans. Activated protein C (APC) is generated from the PC zymogen through proteolytic activation by thrombin. APC inhibits thrombin generation by inactivating activated factors V and VIII via limited proteolysis. In addition to its anticoagulant function, APC also exhibits potent cytoprotective and anti-inflammatory properties. We have identified a young male with multiple-site thrombosis, who carries a heterozygous mutation c.1151A > G,p.Asn384Ser(N384S) in PC. Although this mutation has been previously documented, limited functional research has been conducted to elucidate its pathogenesis.To elucidate the functional alternations of the N384S mutant protein C and delineate the molecular mechanism underlying thrombosis in the patient carrying this mutation.We expressed the recombinant PC-N384S in mammalian cells and characterized its properties in established coagulation and anti-inflammatory assay systems.The expression level of the PC-N384S was reduced to approximately 7% of that observed for PC-WT. The activation of PC-N384S by thrombin or thrombin–thrombomodulin (TM) complex was significantly impaired, although the addition of TM exhibited a slight enhancement in the activation process. In terms of cleaving a chromogenic substrate, the catalytic efficiency reduced to approximately 50% of that observed in the wild type. In addition, in comparison with APC-WT, APC-N384S demonstrated a pronounced decline in amidolytic activity following an extended incubation period at 37°C. APC-N384S exhibited slightly impaired anticoagulant activity in either FVa inhibition assay or plasma-based assay systems. Furthermore, anti-inflammatory activity of APC-N384S was dramatically impaired as determined by evaluating the barrier-protective effect.The Asn384Ser mutation impairs both the anticoagulant and barrier-protective activities of protein C, thereby increasing the thrombosis risk in the heterozygous young male.
Keywords: protein C; mutation; thrombosis; anticoagulant